Quantifying the electron donating capacities of sulfide and dissolved organic matter in sediment pore waters of wetlands. Issue 5 (3rd May 2017) - Wallace, Grant C.; Sander, Michael; Chin, Yu-Ping; Arnold, William A.
Abstract : The measured electron donating capacity of sulfidic wetland pore waters is similar for three different methods. Abstract : Electron donating capacity (EDC) values were determined for a set of pore water samples collected from the sediments of four separate wetlands in the Cottonwood Lakes Study Area in Jamestown, ND by mediated electrochemical analysis, reaction with substituted nitro(so)benzenes, and calculation based on measured organic carbon and sulfide concentrations. The samples were taken from four hydrologically connected and increasingly sulfidic wetlands within the study site. Parallel trends in EDC values related to hydrologic conditions and to in situ reduced sulfur content were observed by all three methodologies. In particular, it was found that sulfide and dissolved organic matter (DOM) are the primary and secondary reductants, respectively, in these systems. The efficacy of these reductants in transforming organic contaminants, however, is largely driven by native pore water reduced sulfur content. Manipulation of the systems demonstrate that while DOM is capable of reducing highly oxidized contaminants or reactive intermediates, this likely only occurs once the reducing capacity of the sulfide is exhausted. Sulfide therefore was the dominant electron donor in the pore water samples.